Scientific opinion on the extension of uses of quillaia extract (E 999) as a food additive - EFSA Panel on Food Additives and Flavourings (FAF); Laurence Castle; Monica Andreassen; Gabriele Aquilina; Maria Lourdes Bastos; Polly Boon; Biagio Fallico; Reginald FitzGerald; Maria Jose Frutos Fernandez; Bettina Grasl‐Kraupp; Ursula Gundert‐Remy; Rainer Gürtler; et al. (EFSA Journal)
Abstract The EFSA Panel on Food Additives and Flavourings (FAF Panel) evaluated the safety of the extension of uses of quillaia extract (E 999) as a food additive in food supplements supplied in a solid or liquid form, excluding food supplements for infants and young children. Quillaia extract (E 999) was re‐evaluated in 2019 by the EFSA FAF Panel, which derived an acceptable daily intake (ADI) of 3 mg saponins/kg bw per day for E 999, while in 2024 a follow‐up of the re‐evaluation was published by the FAF Panel, recommending some modifications of the existing EU specifications for quillaia extract (E 999). Currently, quillaia extract (E 999) is authorised in two food categories (FCs) i.e. FC 4.1.4 ‘Flavoured drinks’ and FC 14.2.3 ‘Cider and perry’ (excluding cidre bouché, cydr jakościowy, perry jakościowe, cydr lodowy, perry lodowe). A ‘food supplements consumers only’ scenario was calculated for this opinion considering the proposed extension of uses, together with the current authorised uses at both the maximum permitted level (MPLs) and the typical reported use levels of quillaia extract (E 999) at the time of the 2019 re‐evaluation. The Panel concluded that the exposure estimates using the typical reported use levels for the currently authorised food categories and considering the proposed extension of uses for E 999 in FC 17.1 ‘Food supplements supplied in a solid form, excluding food supplement for infants and young children’ and FC 17.2 ‘Food supplements supplied in a liquid form, excluding food supplement for infants and young children’, if authorised, would not result in an exceedance of the ADI in any population group.